2023
DOI: 10.3177/jnsv.69.28
|View full text |Cite
|
Sign up to set email alerts
|

Association of Folic Acid Supplementation, Dietary Folate Intake and Serum Folate Levels with Risk of Gestational Diabetes Mellitus: A Matched Case-Control Study

Abstract: Periconceptional folate supplementation is prevalent, raising concerns about possible side effects. The aim of this study was to investigate the associations of folic acid supplementation, dietary folate, serum folate with gestational diabetes mellitus (GDM) risk. In this matched case-control study, 81 pregnant women with GDM (cases) and 81 pregnant women with non-GDM (controls) were identifi ed through age difference (Յ3 y) and parity (Both primipara or multipara women) matching, and serum folate levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 40 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…Multiple studies have been conducted to investigate the association between FA intake, circulating folate levels, MTHFR polymorphisms, and the risk of GDM. [10][11][12][13][14][15][16][17] However, there is currently no consensus on the relationship between FA intake and GDM. 18 Some studies have provided evidence supporting the connection between pregnancies lacking FA supplementation and an increased risk of GDM.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Multiple studies have been conducted to investigate the association between FA intake, circulating folate levels, MTHFR polymorphisms, and the risk of GDM. [10][11][12][13][14][15][16][17] However, there is currently no consensus on the relationship between FA intake and GDM. 18 Some studies have provided evidence supporting the connection between pregnancies lacking FA supplementation and an increased risk of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…18 Some studies have provided evidence supporting the connection between pregnancies lacking FA supplementation and an increased risk of GDM. 10,11 Conversely, contradictory findings have suggested that excessive FA intake may also be associated with a higher risk of GDM. 15,16 We did not find a correlation between FA intake and GDM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations